MINERALOGY AND PETROLOGY OF LATE CRETACEOUS - PALEOGENE VOLCANICS IN CENTRAL KAMCHATKA - Flerov G.B.; Seliverstov V.A. (My University, 2000)
This study of minerals from the Late Cretaceous potassic volcanic rocks of the Kirganik Suite from the Sredinnyi Range of Central Kamchatka provided a basis for affiliating these rocks with two series: (1) a plagioclase shoshonite series including basalts, subalkaline high-Ti basalts, trachybasalts, trachybasaltic andesites, tephrites, latites, and essexites; and (2) a potassic alkaline series without plagioclase including absarokites, shonkinites with leucite, and orthoclase pyroxenites. Leucite of liquidus crystallization was discovered in the shonkinite porphyry. This proves the primary magmatic origin of the potassic alkalinity of the magmas, from which the pre-orogenic volcanic rocks had been derived. The formation of the chemical and mineralogical compositions of the rocks had been influenced by various petrogenic processes: fractionation, magma mixing, and the addition of potassium by transmagmatic fluids. The petrology of the rocks suggests the rocks of both series to be syngenetic. A distinct compositional heterogeneity of pyroxenes from the rocks of the shoshonite series can be explained by their crystallization in a wide range of P-T variation.
Keywords: Cretaceous; Paleogene; Кайнозой::Палеоген; Mesozoic::Cretaceous; Cenozoic::Paleogene; Мезозой::Меловая